The Influence of Servant Leadership and Interpersonal Communication on the Organizational Commitment of Astra Dealer Employees Padang Jati Bengkulu City - Ratnawili, Ratnawili; Arini, Eti; Fitri, Marliza Ade (JURNAL BISNIS STRATEGI, 2023)
The research aimed to explore the impact of Leadership and Interpersonal Communication on the Organizational Commitment of Astra Motor Padang Jati employees in Bengkulu City. The study employed a quantitative approach, encompassing all 40 employees of Astra Motor Padang Jati Bengkulu City, chosen through total sampling. Data collection involved observation and questionnaires, and analysis was performed using the Multiple Linear Regression Test. The results highlighted the significant influence of Leadership on organizational commitment, supported by t-test findings (t_hit> t_ (α / 2) (3.493> 2.026, sig α = 0.001 <0.050), rejecting H_0 and accepting H_a. Similarly, Interpersonal Communication had a significant impact on organizational commitment, confirmed by t-test results (t_hit> t_ (α / 2) (2.689> 2.026, sig α = 0.011 <0.050), rejecting H_0 and accepting H_a. Furthermore, the combined effect of Servant Leadership (X_1) and Interpersonal Communication (X2) on Organizational Commitment (Y) at Astra Motor Padang Dealer, Bengkulu City was significant (F_count> F_Tabel, 53.112> 2.249, sig α = 0.000 <0.050), rejecting H_0 and accepting H_a. The coefficient tests revealed R = 0.864 and R ^ 2 = 0.742, indicating that 74.2% of Organizational Commitment (Y) at Astra Motor Dealer Padang Jati Bengkulu City was influenced by Servant Leadership (X_1) and Interpersonal Communication (X2), leaving 25.8% influenced by other unexamined variables.